On a New Characterization of Some Class Nonlinear Eigenvalue Problem - Lutfi Akin (Advances in Mathematical Physics)
A normal mode analysis of a vibrating mechanical or electrical system gives rise to an eigenvalue problem. Faber made a fairly complete study of the existence and asymptotic behavior of eigenvalues and eigenfunctions, Green’s function, and expansion properties. We will investigate a new characterization of some class nonlinear eigenvalue problem.